2018
DOI: 10.1002/acr.23346
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hepatitis B Virus Reactivation in Patients With Inflammatory Arthritis Receiving Disease‐Modifying Antirheumatic Drugs: A Systematic Review and Meta‐Analysis

Abstract: We found that the HBV reactivation rate in inflammatory arthritis patients receiving DMARDs was low in resolved patients and moderate in patients with chronic HBV infection. Further, lower rates were observed in patients with chronic HBV infection who were using antiviral prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
(151 reference statements)
3
17
0
2
Order By: Relevance
“…In contrast, none of HBsAg‐positive patients who had received pre‐emptive antiviral therapy developed rHBV. Our data support previous findings that antiviral therapy can reduce the incidence or severity of rHBV . As Hsu et al showed that in a computerized alert system providing excellent HBV screening and effectively preventing rHBV in cancer patients receiving chemotherapy, HBV screening is needed, and antiviral therapy should be given in HBsAg‐positive patients before starting RTX therapy.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, none of HBsAg‐positive patients who had received pre‐emptive antiviral therapy developed rHBV. Our data support previous findings that antiviral therapy can reduce the incidence or severity of rHBV . As Hsu et al showed that in a computerized alert system providing excellent HBV screening and effectively preventing rHBV in cancer patients receiving chemotherapy, HBV screening is needed, and antiviral therapy should be given in HBsAg‐positive patients before starting RTX therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Besides their well-established role in ameliorating control of disease activity, bDMARDs have been associated with safety concerns. Infections (including tuberculosis and opportunistic) [ 14 , 15 ], skin cancers [ 16 ], demyelinating leukoencephalopathy [ 17 ] and hepatitis B reactivation [ 18 ] have been reported during therapy with bDMARDs in clinical trials and real-life studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inhibition of TNF can lead to enhanced viral replication, leading to reactivation in resolved HBV/occult HBV infection (HBV surface antigen [HBsAg] negative and antibody to HBV core antigen positive) and in inactive carriers (HBsAg positive, HBV e‐antigen negative, anti‐HBe positive, with viral loads <2000 IU/mL and normal range of alanine aminotransferase [ALT]) or worsening of the active disease (HBsAg positive, with viral loads >2000 IU/mL and with constant or periodic ALT increase). The most recent meta‐analysis of observational studies found the rate of HBV reactivation in inflammatory arthritis patients with resolved hepatitis B after TNF inhibitor treatment (n = 629) to be 1.4%, similar to the rate during nonbiologic DMARDs treatment (1.7%) . In a group of patients with chronic HBV infection (inactive carriers and with active disease), rates of reactivation/disease worsening significantly differ among those who received simultaneously with TNF inhibitor prophylaxis/treatment for HBV (n = 57) and those who did not (n = 64; 4.4% vs 15.6%, respectively).…”
Section: Infectionsmentioning
confidence: 92%
“…The most recent meta-analysis of observational studies found the rate of HBV reactivation in inflammatory arthritis patients with resolved hepatitis B after TNF inhibitor treatment (n = 629) to be 1.4%, similar to the rate during nonbiologic DMARDs treatment (1.7%). 52 In a group of patients with chronic HBV infection (inactive carriers and with active disease), rates of reactivation/disease worsening significantly differ among those who received simultaneously with TNF inhibitor prophylaxis/treatment for HBV (n = 57) and those who did not (n = 64; 4.4% vs 15.6%, respectively). It is hard, however, to estimate rates of HBV reactivations after TNF inhibitors in patients with ankylosing spondylitis.…”
Section: Viral Hepatitismentioning
confidence: 96%